Ethinyl estradiol sulfate acts without fluid resuscitation through estrogen receptors to rapidly protect the cardiovascular system from severe hemorrhage. Issue 2 (February 2021) - Hubbard, William J.; Yang, Shaolong; Chaudry, Irshad H.
Abstract : BACKGROUND: Our in vivo rodent and pig model evidenced that estrogen and its derivative, ethinyl estradiol sulfate (EES), promote survival following hemorrhagic shock. To determine its mechanism, we first confirmed EES binding to estrogen receptor (ER) and improving/restoring cellular signaling, countering the assumption that EES, an ethinyl estradiol metabolite, is inactive. In addition, we examined if EES acts rapidly, consistent with nongenomic signaling. We selected the biomarkers of cardiovascular performance, reduction of apoptosis and proinflammatory responses, and elaboration of nitric oxide (NO) to validate efficacy. METHODS: A rat trauma-hemorrhage model, consisting of a midline laparotomy and controlled bleeding (60% blood loss) without fluid resuscitation, was used. At 30 minutes after hemorrhage, heart performance was monitored, and Western blots were used to quantify biochemical analytes. The specificity of EES for ER was profiled with ER antagonists. Binding studies by Sekisui XenoTech (Kansas City, KS) determined an LD50 value for EES binding the rat ER. RESULTS: The EES IC50 value was 1.52 × 10 −8 Mol/L, consistent with pharmacologic efficacy. Ethinyl estradiol sulfate raised mean arterial pressure and ±derivative of pressure over time (dP/dT) significantly (but did not fully restore) within a 30-minute window. Levels of apoptosis and activation of NF-κB were dramatically reduced, as was elaboration of nitric oxide (NO) by inducible nitric oxide synthase. Phospho-endothelial nitric oxide synthase (eNOS) was restored to physiological levels. The restoration of cellular signaling occurs before restoration of cardiac contractility. CONCLUSION: Ethinyl estradiol sulfate is a potent drug for improving heart performance, which also dramatically reduces damage by apoptosis, proinflammatory activity, and NO production, validating that EES can blunt multiple harmful outcomes arising from hypoxia and hypovolemia. The actions are dependent on receptor engagement, where specificity is confirmed by ER antagonists. The constraint of a 30-minute sampling window affirms that the responses are nongenomic and very likely restricted to cell-surface receptor engagement. The rapidity of these responses makes EES promising for intervention in the "golden hour."